US INVESTMENTS IN PRIORITY SECTORS OF THE ECONOMY OF KAZAKHSTAN - Shakulikova G.Т.; Yerzhanova, Zh.K.; Gabbassova, Zh.Zh.; Karabassov, R.A.; Abdykarimova A.Т.; Kuangaliyeva, T.K. (Scientific Journal of Pedagogy and Economics, 2020)
In the conditions of self-isolation, a small and medium business suffered as a result of a pandemic, however, large business remained afloat due to large “long money”. Large business in Kazakhstan is mainly a raw material business, i.e., the mining industry, as a priority, has not suspended its activities. The tasks in the field of attracting investment remained the same. For Kazakhstan, in the direction of attracting foreign investment, firstly, it is worth identifying competitive sectors of the economy. Secondly, clearly understand the key factors in the development of these industries. Thirdly, to conduct a comparative analysis and assess the advantages and disadvantages in relation to other countries, which will be the main competitors in this industry. Fourth, identify potential investors. Fifth, optimize the activities of the coordinating agency or body that is responsible for investments in Kazakhstan. For US investors, the stock market in Kazakhstan is very small. It presents mainly companies in the mining and financial sectors of the economy, as well as the public sector. The limited financing opportunities in the stock market do not allow providing higher returns on investment funds, and this in turn negatively affects the influx of potential investors and investors.